Pitfalls in the Interpretation of Publications about Endoscopic Submucosal Dissection of Early Gastric Cancer with Undifferentiated-Type Histology - Bang, Chang Seok (Clin Endosc, 2019)
Endoscopic submucosal dissection (ESD) is a standard treatment for patients with gastrointestinal neoplasms with a negligible risk of lymph node metastasis. ESD enables en bloc resection of gastrointestinal neoplasms and organ preservation, thereby, avoiding surgical treatment. Although small (<2 cm) intramucosal early gastric cancer with undifferentiated-type histology (EGC-UH) without ulceration is included in the expanded criteria for ESD, controversies remain due to different biology and characteristics compared to EGC with differentiated-type histology. The authors previously presented studies about the technical feasibility of ESD for these lesions using a meta-analysis and retrospective multicenter analysis. However, many pitfalls were identified in the interpretation of studies analyzing histologic discrepancy, mixed-type histology, criteria-based analysis of therapeutic outcomes, interpretation of curative resection, and long-term clinical outcomes. In this review, the authors discuss pitfalls in the interpretation of publications on ESD for EGC-UH.